Digital Marketing for Consumer Repurchases - Yanpitak, Pittayush; Tabsuri, Patcharee; Teerachaiyapat, Chainarin (Interdisciplinary Academic and Research Journal, 2023)
Today's business operations are the dimension of social e-commerce, online trade, which can be divided into 2 components: The first part is a social network that will act as a website that can add commercial features that allow for advertising and buying, and selling. And the second part is that e-commerce has enhanced the ability of social networks to enhance business competitive advantages. Thus, this article is a study of the key factors leading to consumer repurchase behavior in digital societies Digital marketing approach to supporting consumer repurchases The study found that 1) Consumers are critical to meeting their needs; There are four marketing components: product, price, distribution channel, and marketing promotion. It contributes to the repurchase decision. and 2) the key digital marketing approach is (1) marketing that values the perceived value of the product; Reasonable pricing compared to quality It is suitable compared to other stores and is suitable for economic conditions. (2) The service provided by the shop must be of high quality and consistent service. Professional in-service. The website should be modern, beautiful, and eye-catching. The process of ordering, shipping, and payment is hassle-free, as well as providing a full range of products. (3) Product quality Product uniqueness and product certification marks (4) Good quality of marketing communications, quality placing Marketing strategies using search marketing Use keywords to name your site so that your site is at the top of your search page. Online strategy for advertising through Facebook, including video clips on YouTube.